Draft Annual Plan 1971-72 Government of Himachal Pradesh - Planning Commission (Planning Commission, 1971)
Right in the lap of Himalayan ranges, Himachal Pradesh is situated in the extreme north-west of India. It is surrounded by Jammu and Kashmir State in the north-west, Tibet in the east, Uttar Pradesh in the south-east and by the Punjab and Haryana in the west and south. the Pradesh is one of the most picturesque regions in the country, lying between 30° 22' to 330 12' north latitude and 750 4'71 to 730 4 east longitude. The territory is entirely with altitude ranging from 1500 ft to 21,000 ft above sea level. the climate in the southern parts of the Pradesh is almost as hot as in the plains. the winter in the north region is marked by bracing cold and heavy snow-falls.
Government of Himachal Pradesh, Planning and Evaluation Department